2009
DOI: 10.4161/cc.8.5.7709
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 1q gain is not associated with a poor outcome in childhood medulloblastoma: Requirements for the validation of potential prognostic biomarkers

Abstract: (2009) Chromosome 1q gain is not associated with a poor outcome in childhood medulloblastoma: Requirements for the validation of potential prognostic biomarkers,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…54 In another study comprising 73 cases, evidence for relationship between chromosome 1q gain and poor survival was not detected. 21 In our study, we found no difference in survival in patients with and without chromosome 1q aberration.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…54 In another study comprising 73 cases, evidence for relationship between chromosome 1q gain and poor survival was not detected. 21 In our study, we found no difference in survival in patients with and without chromosome 1q aberration.…”
Section: Discussioncontrasting
confidence: 57%
“…Similar finding showing the lack of chromosome 1q abnormality and adverse clinical outcome has been reported. 21 The results suggest that chromosome 1q aberration contributes to KIF14 upregulation and it is a common event in MB.…”
Section: Gain Of Chromosome 1q Is a Frequentmentioning
confidence: 88%
“…Over the past three decades, multiple markers have been developed that hold promise for better prognostic stratification and more individualized therapy for pediatric MB [6][7][8][9]. Recent gene-expression profiling studies have suggested four molecular subtypes of MB, each of which is characterized by a distinct genetic profile, distinct activation of oncogenic pathways, and varied clinical outcomes.…”
Section: Introductionmentioning
confidence: 98%